1997
DOI: 10.1046/j.1365-2958.1997.6011973.x
|View full text |Cite
|
Sign up to set email alerts
|

uvrD mutations enhance tandem repeat deletion in the Escherichia coli chromosome via SOS induction of the RecF recombination pathway

Abstract: SummaryIt has previously been shown that recombination between tandem repeats is not significantly affected by a recA mutation in Escherichia coli. Here, we describe the activation of a RecA-dependent recombination pathway in a hyper-recombination mutant. In order to analyse how tandem repeat deletion may proceed, we searched for mutants that affect this process. Three hyper-recombination clones were characterized and shown to be mutated in the uvrD gene. Two of the mutations were identified as opal mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…The expression of sulA-lac in a uvrD strain remained elevated despite introduction of mutations in recB, recF, recQ, or ruvABC (data not shown). Substantially similar results have also been described earlier (3).…”
Section: Vol 182 2000 Uvrd-lon Incompatibility In E Coli 3153supporting
confidence: 80%
See 1 more Smart Citation
“…The expression of sulA-lac in a uvrD strain remained elevated despite introduction of mutations in recB, recF, recQ, or ruvABC (data not shown). Substantially similar results have also been described earlier (3).…”
Section: Vol 182 2000 Uvrd-lon Incompatibility In E Coli 3153supporting
confidence: 80%
“…Another substrate of the Lon protease is the cell septation inhibitor SulA, whose synthesis is induced during the SOS response; as a consequence, lon mutants are known to be sensitive to SOS-inducing agents (reviewed in references 23 and 55). At least some uvrD mutations have been shown earlier to induce the SOS response (3,25,38), and we therefore tested the hypothesis that the uvrD-lon combination is rendered inviable because Lon becomes essential to degrade the increased concentration of SulA in the uvrD mutant background. (i) Using sulA-lac expression as a measure of SOS induction, we found that the uvrD400::Tn10dTet insertion (which is lon incompatible) caused a moderate (5-fold) induction of the SOS regulon, as against the 70-fold increase observed in a fully derepressed (⌬lexA) strain ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…3). Stimulation of tandem repeat instability in a uvrD mutant was previously shown to be caused by an increase in RecF-mediated recombination (21) and this result may relate to the antirecombination role of the UvrD protein (22).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Dda may mediate deletion mutagenesis in response to DNA damage, and overproduction of Dda might promote deletions between repetitive sequences. Indeed, overproduction of UvrD, a helicase unrelated to Dda, promotes deletions between tandem repeats via induction of the RecF recombination pathway (28).…”
Section: Resultsmentioning
confidence: 99%